AMPEL HERITAGE TOURISM AREA IN THE CONTEXT OF SUSTAINABILITY - Galuh Fajarwati; Komang Ayu Laksmi Harshinta Sari; Faniah Shafira Amir Ishak (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2020)
The rapid growth of the city of Surabaya greatly affects the physical development of urban areas, especially tourist areas. Ampel region is defined as a region of religious tourism and cultural heritage buildings by the city government by Mayors Number: 188.45 / 251 / 402.1.104 / 1996. The area has potential for tourism and the economy are high, but a blend of tourist areas, especially economic and trade area in the region is not complementary. So that the necessary processing and review of the Ampel area to harmonize trade and economic progress in the region to continue to support the function of the area of religious tourism. The method used by the descriptive approach and using the criteria of sustainable development goals, four pillars of sustainability. Urban heritage plan will be developed especially in the area of environmental Ampel Mosque and street vendors (PKL) in the area around the mosque. The basic form of the tourist areas has a broad scope, involving the regional areas, especially residential areas that will be affected negatively or positively on the system of the tourist area. However, this can improve the economy and income mainly local communities. Review and structuring this region will travel Ampel's impact on the pattern of people's lives around. Results from this research that some of the physical elements, such as infrastructure (circulation and parking), open space,